A T > G Mutation in the NR5A2 Gene Is Associated With Litter Size in Hu Sheep Through Upregulation of Promoter Activity by Transcription Factor MTF-1 - Li, Yinxia; Zhang, Jun; Qian, Yong; Meng, Chunhua; Wang, Huili; Zhong, Jifeng; Cao, Shaoxian (Frontiers in Genetics, 2019)
Nuclear receptor subfamily 5 group A member 2 (NR5A2), also referred to as LRH-1 or FTF, is an orphan nuclear hormone receptor that is involved in regulating embryonic development, ovarian granulosa cell differentiation, gonadal sex differentiation, and steroidogenesis in mammals. However, little is known about how NR5A2 regulates reproduction in sheep. In this study, we amplified the promoter sequence of NR5A2 and determined that its core promoter region ranged from -721 nt to -281 nt. A T>G polymorphism at -700 nt was detected in the core promoter region. Association analysis found that the litter sizes of Hu ewes at their second and average parities with genotype GG (2.20±0.20 and 1.97±0.06, respectively) were significantly higher than those of ewes with genotype TG (1.68±0.10 and 1.74±0.05, respectively) (p<0.05) and TT (1.67±0.10 and 1.62±0.06, respectively) (p<0.05). The litter size of Hu ewes at their third parity with genotype GG (2.10±0.10) was significantly higher than that of ewes with genotype TT (1.56±0.12) (p<0.05). A luciferase assay showed that the -700G allele increased the luciferase activity relative to the -700T allele. Furthermore, the -700T>G polymorphism created a novel binding site for metal-regulatory transcription factor 1 (MTF-1). A competitive EMSA assay confirmed that MTF-1 specifically bound with the G-type promoter of NR5A2. An overexpression experiment demonstrated that MTF-1 was involved in the alteration of NR5A2 transcription activity and further increased NR5A2 gene mRNA expression. Our findings revealed that the -700T>G polymorphism promoted NR5A2 expression due to the positive effects on NR5A2 gene transcription activity by MTF-1, and thereby increased fecundity in Hu sheep.